Land use change: Methodological approach to understand the interactions Nature/Society in coastal areas - Lourenço, Nelson (2012)
The report being presented now is the result of a study on Land Use Change: Methodological Approach to Understand the Interactions Nature / Society in Coastal Areas. This study has been carried out within the framework of a research contract funded by the Directorate General Joint Research Centre, Agriculture and Regional Information Systems, Unit Space Applications Institute in which we specially recognise the enthusiastic support of the technical responsible, Mrs. Vanda Perdigão. A feature of the work conducted during the eight months has been the important collaboration of the Centro Nacional de Informação Geográfica, particularly Mr. João Reis Machado, who made possible the use of statistical information with a high level of spatial division, which was kindly authorised by the Instituto Nacional de Estatística. A methodological effort should be highlighted, specifically in terms of the difficulties of compatibility of the statistical and digital data. The existence or non-existence of databases (statistical, from official bodies and available on a digital support) determines the different usage of analysis instruments. With regard to the use of GIS, it should be stressed that this study was only possible because of the existence of digitalised data for Portugal, in the Corine and Lacoast programmes.